A Mixed-Methods Study on Acceptability, Tolerability, and Substitution of Brown Rice for White Rice to Lower Blood Glucose Levels among Nigerian Adults - Adebamowo, Sally N.; Eseyin, Olabimpe; Yilme, Susan; Adeyemi, David; Willett, Walter C.; Hu, Frank B.; Spiegelman, Donna; Adebamowo, Clement A.; , The Global Nutrition Epidemiologic Transition Initiative (Frontiers in Nutrition, 2017)
Background: Whole-grain products such as brown rice have been associated with lower risk of metabolic disorders including diabetes. We examined the acceptability and tolerability of substituting brown rice for white rice and the feasibility of introducing brown rice into the diet through a long-term trial to lower the risk of type 2 diabetes. Methods: Fifty-one adults residing in Abuja, Nigeria, participated in this study. Using purposeful sampling for focus group discussions, participants were enrolled based on their age (19-25y vs. 40-60y) and body mass index (BMI) (normal weight vs. overweight/obese). Participants tasted four meals with different constitution of brown and white rice (25%:75%, 50%:50%, 75%:25% and 100% brown rice). Twelve focus group discussions were conducted, 6 before and 6 after the food tasting. Two-hour postprandial blood glucose was measured after consumption of each rice meal. Results: The mean age of the participants was 39 (±14) years, their mean BMI was 25.6 (±5.2) and about half of them were male. Most of the participants (61%) reported rice was their main source of carbohydrate, and 67% consumed rice at least 5 times/week. Before the food tasting, participants considered white polished rice superior to brown rice with regard to quality, taste and nutritional value. After the food tasting, most of the participants (49%) indicated a preference for the 100% brown rice, 19% preferred the 25% brown rice, 18% preferred the 50% brown rice and 7% preferred the 75% brown rice meals. Factors that may affect the acceptability of brown rice include its appearance, longer cooking time, cost, limited availability and poor appreciation of its nutritional value. In general, 2-hour post-prandial glucose levels were lower, after consumption of meals with higher proportion of brown rice. Conclusions: This study provides valuable insight into the acceptability of brown rice as a substitute for white rice in Nigeria. If confirmed in larger studies, these results highlight the importance of increasing awareness on the nutritional value of brown and support the rationale for conducting a large-scale intervention trial to examine the effect of brown rice consumption on blood sugar levels among Nigerians.